Mutation of an L-Type Calcium Channel Gene Leads to T Lymphocyte Dysfunction - Fenninger, Franz (Front Immunol, 2019)
Calcium (Ca(2+)) is a vital secondary messenger in T lymphocytes regulating a vast array of important events including maturation, homeostasis, activation, and apoptosis and can enter the cell through CRAC, TRP, and Ca(V) channels. Here we describe a mutation in the L-type Ca(2+) channel Ca(V)1.4 leading to T lymphocyte dysfunction, including several hallmarks of immunological exhaustion. Ca(V)1.4-deficient mice exhibited an expansion of central and effector memory T lymphocytes, and an upregulation of inhibitory receptors on several T cell subsets. Moreover, the sustained elevated levels of activation markers on B lymphocytes suggest that they are in a chronic state of activation. Functionally, T lymphocytes exhibited a reduced store-operated Ca(2+) flux compared to wild-type controls. Finally, modifying environmental conditions by herpes virus infection exacerbated the dysfunctional immune phenotype of the Ca(V)1.4-deficient mice. This is the first example where the mutation of a Ca(V) channel leads to T lymphocyte dysfunction, including the upregulation of several inhibitory receptors, hallmarks of T cell exhaustion, and establishes the physiological importance of Ca(V) channel signaling in maintaining a nimble immune system.